Impact of vaccination on hospitalization and mortality from COVID-19 in patients with primary and secondary immunodeficiency: The United Kingdom experience - Shields, Adrian M.; Tadros, Susan; Al-Hakim, Adam; Nell, Jeremy M.; Lin, Me Me Nay; Chan, Michele; Goddard, Sarah; Dempster, John; Dziadzio, Magdalena; Patel, Smita Y.; Elkalifa, Shuayb; Huissoon, Aarnoud; et al. (Frontiers in Immunology, 2022)
Background Individuals with primary and secondary immunodeficiency (PID/SID) were shown to be at risk of poor outcomes during the early stages of the SARS-CoV-2 pandemic. SARS-CoV-2 vaccines demonstrate reduced immunogenicity in these patients. Objectives To understand whether the risk of severe COVID-19 in individuals with PID or SID has changed following the deployment of vaccination and therapeutics in the context of the emergence of novel viral variants of concern. Methods The outcomes of two cohorts of patients with PID and SID were compared: the first, infected between March and July 2020, prior to vaccination and treatments, the second after these intervention became available between January 2021 and April 2022. Results 22.7% of immunodeficient patients have been infected at least once with SARS-CoV-2 since the start of the pandemic, compared to over 70% of the general population. Immunodeficient patients were typically infected later in the pandemic when the B.1.1.529 (Omicron) variant was dominant. This delay was associated with receipt of more vaccine doses and higher pre-infection seroprevalence. Compared to March-July 2020, hospitalisation rates (53.3% vs 17.9%, p<0.0001) and mortality (Infection fatality rate 20.0% vs 3.4%, p=0.0003) have significantly reduced for patients with PID but remain elevated compared to the general population. The presence of a serological response to vaccination was associated with a reduced duration of viral detection by PCR in the nasopharynx. Early outpatient treatment with antivirals or monoclonal antibodies reduced hospitalisation during the Omicron wave. Conclusions Most individuals with immunodeficiency in the United Kingdom remain SARS-CoV-2 infection naïve. Vaccination, widespread availability of outpatient treatments and, possibly, the emergence of the B.1.1.529 variant have led to significant improvements in morbidity and mortality followings SARS-CoV-2 infection since the start of the pandemic. However, individuals with PID and SID remain at significantly increased risk of poor outcomes compared to the general population; mitigation, vaccination and treatment strategies must be optimised to minimise the ongoing burden of the pandemic in these vulnerable cohorts.